The new trends of the student movement in Nicaragua (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
This essay reflects on the student movement and its dynamics in Nicaraguan society. Showing clearly your participation in the social agenda from its foundation to the present. The current trend shown by the movement is towards social and environmental actions. It shows a student movement participate in the countrys political agenda, with increasingly concrete activities in the social and environmental spheres. The essay combines participant observation, such as theoretical reflections, betting on a reflexive critical narrative.
Keywords: student movement; UNEN; social agenda; political anthropology